2020
DOI: 10.1038/s41392-020-0108-z
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of Notch and FLT3 produces synergistic cytotoxic effects in FLT3/ITD+ acute myeloid leukemia

Abstract: Internal tandem duplication (ITD) mutations of FMS-like tyrosine kinase-3 (FLT3) are the most frequent genetic alterations in acute myeloid leukemia (AML) and predict a poor prognosis. FLT3 tyrosine kinase inhibitors (TKIs) provide short-term clinical responses, but the long-term prognosis of FLT3/ITD + AML patients remains poor. Notch signaling is important in numerous types of tumors. However, the role of Notch signaling in FLT3/ITD + AML remains to be elucidated. In the current study, we found that Notch si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
(51 reference statements)
1
12
0
Order By: Relevance
“…Therefore, CD44v6 expression was associated with FLT3 mutations or FLT3 overexpression which was also proved by our follow‐up experiments. Using the CRISPR/Cas9 system, we knocked in a 21‐bp ITD fragment in wild‐type SKM‐1 cells and named the knock‐in clone SKM‐1‐FLT3 21 . Compared to SKM‐1 cells, SKM‐1‐FLT3 cells significantly overexpressed FLT3 mRNA and CD44v6 (Figure 1A,B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CD44v6 expression was associated with FLT3 mutations or FLT3 overexpression which was also proved by our follow‐up experiments. Using the CRISPR/Cas9 system, we knocked in a 21‐bp ITD fragment in wild‐type SKM‐1 cells and named the knock‐in clone SKM‐1‐FLT3 21 . Compared to SKM‐1 cells, SKM‐1‐FLT3 cells significantly overexpressed FLT3 mRNA and CD44v6 (Figure 1A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Using the CRISPR/Cas9 system, we knocked in a 21-bp ITD fragment in wild-type SKM-1 cells and named the knock-in clone SKM-1-FLT3. 21 Compared to SKM-1 cells, SKM-1-FLT3 cells significantly overexpressed FLT3 mRNA and CD44v6 (Figure 1A,B).…”
Section: Expression Of Cd44v6 On Tumour Cellsmentioning
confidence: 93%
“…The Notch signaling pathway is a functional pathway that controls cell survival, proliferation, differentiation, apoptosis, migration, and invasion, and is involved in the determination of cell biological functions in both normal and pathological tissues 19 21 . Several studies have revealed the regulatory effect of the Notch signaling pathway in multiple cancers, including breast cancer 22 , colorectal cancer 23 , acute myeloid leukemia 24 , and ALL 25 . Indeed, Notch signaling pathway inhibitors, such as gamma-secretase inhibitors, have been considered as promising tools for cancer therapy 24 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the regulatory effect of the Notch signaling pathway in multiple cancers, including breast cancer 22 , colorectal cancer 23 , acute myeloid leukemia 24 , and ALL 25 . Indeed, Notch signaling pathway inhibitors, such as gamma-secretase inhibitors, have been considered as promising tools for cancer therapy 24 , 26 . Additionally, Takam et al described a modulatory effect of the Notch pathway in B-ALL, with Notch pathway suppression leading to increased chemosensitivity of B-ALL cells 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, Notch signaling was upregulated following treatment with FLT3-TKIs, which resulted in alternative ERK activation. The addition of Notch inhibitor (GSI) abrogated the alternative activation of ERK, resulting in extreme repression of ERK activity, thereby showing a synergistic antitumor effect ( Li D. et al, 2020 ). Likewise, lung adenocarcinoma patients with activating EGFR L858R mutation show a better response to TKIs initially but subsequently develop resistance and show increased HES1 protein levels that correlate with shorter progression-free survival ( Bousquet Mur et al, 2020 ).…”
Section: Notch Hedgehog and Wnt Signaling In Resistance To Targeted Therapymentioning
confidence: 99%